Population Density Extraction of Kirkuk City Using Landsat Thermal Band and GIS - Kamalaldin F. Hasan; Iman Ali Shawkat; Qayssar Mahmood Ajaj (Genius Journals, 2022)
Population and population density estimates become more difficult to make in countries with rapid population growth, shifting immigration patterns, and other forms of unpredictable demographic change. It is, therefore, crucial to conduct a population count rapidly and cheaply; one viable option for doing so is to make use of satellite photos that feature thermal bands. We used a method (Spatial Analyst) and an idea from statistics that deals with clusters of data to determine the arithmetic means of the correlations between land surface temperature and population density. This study makes use of 2019 Landsat satellite pictures and population density information collected from the Kirkuk Governorate. The calculated conversion factors were the result of applying spatial analysis and statistical analysis to the 13 regions we provided. 2300.00, 898.65, 830.81, 668.65, 585.49, 559.66, 509.28, 452.69, 412.71, and 241.57 for temperatures of 30.5, 31.5, 32.5, 33.5, 34.5, 35.5, 36.5, 37.5, 38.5, and 39.5 Celsius respectively.
Keywords: Population density; Landsat imagery; thermal bands; GIS